Oral-facial-digital syndrome type IX in a patient with Dandy-Walker malformation. Issue 4 (April 1998) - Nagai, K; Nagao, M; Nagao, M; Yanai, S; Minagawa, K; Takahashi, Y; Takekoshi, Y; Ishizaka, A; Matsuzono, Y; Kobayashi, O; Itagaki, T
Abstract : We report a girl with oral, facial, and digital anomalies including multiple alveolar frenula, lobulated tongue with nodules, a posterior cleft palate, hypertelorism, a prominent forehead with a large anterior fontanelle, and postaxial polydactyly in both hands and the right foot, features compatible with the oral-facial-digital syndrome (OFDS). In addition, she had bilateral microphthalmia, optic disc coloboma, and retinal degeneration with partial detachment, thus establishing a diagnosis of OFDS type IX. Dandy-Walker malformation and retrobulbar cysts were observed on MRI. These additional malformations have not been reported in OFDS type IX. The frequent apnoeic spells which occurred immediately after birth were relieved after cystoperitoneal shunt implantation for hydrocephalus. Considering our case and previous reports of OFDS type IX, including two male sibs, a boy born to consanguineous parents, and three females, inheritance is probably autosomal recessive.